Vision Rehabilitation Therapists Teaching Technology: Association Between Their Age and the Frequency at Which Technology Job Tasks Are Performed. (January 2022) - Connors, Elyse M.; Pavone, Rachel C.
Introduction: This study seeks to examine the association between the age of the Vision Rehabilitation Therapist (VRT) and the frequency at which they carry out technology job tasks. Methods: A secondary data analysis was performed, using chi square to test for an association between the age of the VRT and the frequency at which they carry out 11 specific job tasks related to technology. Results: Age of the VRT was shown to be negatively associated with the frequency at which 6 of the 11 technology job tasks are performed. Discussion: Overall, younger VRTs are teaching access technology at higher frequencies than older VRTs. Newer specific technologies are being taught more often by younger VRTs, such as mobile technologies, voice-controlled devices, and social media. Older technologies such as keyboarding and OCR are being taught at similar frequencies regardless of age. Given the aging population of VRTs and the small number of university VRT programs, it may not be sustainable to rely on recent graduates or younger VRTs to fulfill access training needs for persons with visual impairment. With the availability, affordability, and quick emergence of new technologies, it is critical that all VRTs have access to continuing education to become comfortable and proficient in teaching newer technologies. Implication for Practitioners: Technology training is critical for employment and independence for many persons with vision impairment. Continuing education for VRTs to be comfortable and competent in teaching emerging technologies may be important in ensuring that access technology training is available to all persons with visual impairment.